Evaluation of Reservoir performance Clean Water Distribution in Putat Gede Graha Family - Jonah Swanata; M ikhsan Setiawan (Journal of World Conference (JWC), 2020)
Water is one of the natural resources that is very important for the life of living things, and even becomes the main life for humans. With the existing treatment system and piping network system, Surya Sembada PDAM is expected to be able to meet the community’s clean water needs in Surabaya city. One og crucial things is the performance of reservoir in piped water distribution system from the clean water treatment plant. This study aims to evaluate the reservoir performance of the Surabaya PDAM, specifically the performance of Putat Gede reservoir, which is a distribution reservoir that serves the distribution of clean water to Graha Family Surabaya city. In this study Epanet 2.0 software was used as a hydrodynamic modelling tool. Based on the simulation result, at peak hours 07.00 a.m. reservoir Putat Gede is able to serve the community’s clean water needs. The farthest node has the lowest pressure of 15,45 m, and the lowest water level of the reservoir Putat Gede occurs at 09.00 a.m. which is 3 m. In general, the reservoir is still able to meet community’s clean water needs, especially during peak hours.